Laboratory studies on the feeding of talapia nilotica fed with chicken feed and formulated diets - Hashim Ahmad (Fakulti Pengajian Maritim dan Sains Marin, 2011)
A study on the feeding of T.nilotica fed with chicken feed and formulated diets was conducted at Crop Protection Unit (C.P.U) of Faculty of Fisheries Serdang, Selangor.The study period was about two months commencing at the end of December,1982.